Relationship Of Learning Interest And Learning Mathematics Results - Amiqo Milla; Pratiwi Santi Yastuti (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2020)
This study aims to determine the relationship between interest in learning mathematics and mathematics learning outcomes of class VII students of SMP Dharma Lestari in the 2019/2020 academic year. This correlational study, the population uses all students of grade VII SMP Dharma Lestari as many as 208 students. Probability sampling was used in a population of 40 students. The research instrument in the validity and reliability test was used in data collection, including questionnaires and interview sheets to measure interest in learning mathematics and documentation to measure mathematics learning outcomes. The data analysis technique used Product moment after using the prerequisite for normality and linearity tests, the data were processed using SPSS version 20.0. The results showed that: (1) the seventh grade students' interest in learning mathematics at SMP Dharma Lestari was in the medium category at 70%, (2) the mathematics learning outcomes in the moderate category were 70%, (3) there was a significant and significant relationship between the interest in learning mathematics with VII grade mathematics learning outcomes of SMP Dharma Lestari. Through the results of the Product moment analysis that has been carried out using the SPSS version 20.0 computer program, the r_ (count) value is greater than r_ (table) (0.355> 0.312).